Blended Learning Model to Build Learning Independence Zillennial Generation - Acep Supriadi (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to find out how to optimize the blended learning model in building the learning independence of the Zillennial Generation. This study uses a systematic review method by summarizing the results of primary research to be analyzed and presented so that it can provide accurate, comprehensive and balanced information. The primary research results used were taken from various accredited national and international journals. This is done so that the results obtained are able to answer the research questions thoroughly and accurately. The results showed that the strategy used to develop student learning independence through blended learning was carried out through a shift in the conventional learning paradigm to a digital basis and a change from learning through a one way traffic system to a two way traffic system. Optimizing the development of learning independence through blended learning can be done with five main keys, namely live events, self-paced learning, collaboration, assessment and performance support material